Coronary-Subclavian Steal Syndrome: Percutaneous Approach - Carina Machado; Luís Raposo; Sílvio Leal; Pedro Araújo Gonçalves; Henrique Mesquita Gabriel; Rui Campante Teles; Manuel Sousa Almeida; Miguel Mendes (Case Reports in Cardiology)
Coronary subclavian steal syndrome is a rare ischemic cause in patients after myocardial revascularization surgery. Subclavian artery stenosis or compression proximal to the internal mammary artery graft is the underlying cause. The authors present a clinical case of a patient with previous history of non-ST elevation myocardial infarction, triple coronary bypass, and effort angina since the surgery, with a positive ischemic test. Coronary angiography revealed a significant stenosis of the left subclavian artery, proximal to the internal mammary graft.